Haane Te Rauawa Manahi: The Man, The Moment, The Legacy! - Morrison, Donna Mariana (Auckland University of Technology, 2023)
The research project, titled "Haane Te Rauawa Manahi: the Man, the Moment, the Legacy," is situated within the realm of mātauranga Māori (all encompassng Māori knowledge), incorporating a te ao Māori (Māori worldview), kaupapa Māori (Māori approach) methodologies, and a Māori cultural perspective. It incorporates an exegesis that explores the historiography of an esteemed tupuna (ancestor) while examining the connection between the roles of kaitiaki (spiritual guardian), strategic thinking, and mātauranga Māori. At the heart of this research lies Haane Te Rauawa Manahi (Manahi), representing a deep personal alignment rooted in whakapapa (genealogy / family tree). This link provides a sense of legitimacy, intimacy, and purpose to celebrate a beloved koroua (elderly man), in alignment with expectations of whānau (family), hapū (subtribe), and iwi (tribe). The primary focus is on posthumous efforts to restore the prestigious Victoria Cross (VC) citation award to Manahi for his extraordinary bravery during World War II (WWII). However, inexplicably, it was later downgraded to a Distinguished Conduct Medal (DCM) at the British War Office. The research embraces a te ao Māori worldview while navigating the expectations of Western academia. Through in-depth analysis, it explores the realm of whakapapa, the quest for military recognition, and commemorative celebration. By interweaving these elements, the research seeks to uncover the connections between cultural heritage and the ongoing resonance and legacy of Manahi. Using a pūrākau (story / storytelling) methodology, the research examines the concept of ‘lived legacy’ within a theoretical framework. The aim is to delve into the cognitive and emotional dimensions manifested in the performances of te ao haka (world Māori dance), which vividly bring to life the enduring impact and influence of Manahi in contemporary contexts. To illuminate the life of Manahi and his relationship with Ngāti Whakaue kaitiaki 'Makawe,' the research incorporates targeted interviews, published works, first-person testimonies, and historical events within the context of mātauranga Māori. It is an exploration revealing ariā (physical representation of an atua, visible material emblem of an atua) bestowed by 'Makawe' to spiritually guide Manahi within the theatre of battle. Manahi positions mātauranga Māori as a vital element in understanding a te ao Māori worldview. Additionally, the research incorporates creative elements such as a curated exhibition inside Tamatekapua wharenui (meeting house, large house – main building of a marae), te ao haka performances, and a recording of the ‘whakaaturanga toi whakaari’ (showing of creative art component) at Te Papaīōuru Marae in Rotorua, New Zealand. The exegesis components are integrated into the formal pōwhiri (welcome ceremony) for the exhibition's opening, celebrating Manahi and the 80th Commemoration of the Battle for Takrouna.